Birds - Gray, Samantha; Walker, Sarah (New York : DK, 2002)
A simple introduction to the world of birds.
"Open your eyes to a world of discovery"--Cover.
Includes index.
BL 06/01/02
0508
Keywords: Birds -- Juvenile literature; Birds -- Miscellanea